2010
DOI: 10.4161/psb.5.11.13363
|View full text |Cite
|
Sign up to set email alerts
|

Selective breeding of entomopathogenic nematodes for enhanced attraction to a root signal did not reduce their establishment or persistence after field release

Abstract: Addendum to: Hiltpold I, Baroni M, Toepfer S, Kuhlmann U, Turlings TCJ. Selection of entomopathogenic nematodes for enhanced responsiveness to a volatile root signal helps to control a major root pest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
1
11
0
2
Order By: Relevance
“…After six generations of selective breeding, the selected population of H. bacteriophora responded 4-fold more quickly and strongly to (E)-"-caryophylene than the original one (Hiltpold et al, 2010a). As the selection did not impair the infectiousness of the EPNs (Hiltpold et al, 2010b), both populations were tested in the field and were exposed to two maize cultivars either emitting or lacking the ability to emit (E)-"-caryophylene (Hiltpold et al, 2010a;Rasmann et al, 2005). The application of EPNs significantly reduced the survival of D. v. virgifera irrespective of maize cultivars.…”
Section: Use/selection For a More Competitive Species Or Populationmentioning
confidence: 87%
“…After six generations of selective breeding, the selected population of H. bacteriophora responded 4-fold more quickly and strongly to (E)-"-caryophylene than the original one (Hiltpold et al, 2010a). As the selection did not impair the infectiousness of the EPNs (Hiltpold et al, 2010b), both populations were tested in the field and were exposed to two maize cultivars either emitting or lacking the ability to emit (E)-"-caryophylene (Hiltpold et al, 2010a;Rasmann et al, 2005). The application of EPNs significantly reduced the survival of D. v. virgifera irrespective of maize cultivars.…”
Section: Use/selection For a More Competitive Species Or Populationmentioning
confidence: 87%
“…Yet, this apparent cost was largely compensated for by the higher responsiveness to the root signal. In further study, Hiltpold, Baroni, Toepfer, Kuhlmann, and Turlings (2010b) showed that the selection process had no negative effect on establishment and persistence of fieldreleased EPN. Bai, Shapiro-Ilan, Gaugler, and Hopper (2005) suggested stabilizing beneficial traits in H. bacteriophora through the creation of genetically homozygous inbred lines that can deter beneficial trait decline.…”
Section: Trait Stabilitymentioning
confidence: 91%
“…After six generations of selective breeding, the selected population of H. bacteriophora responded 4-fold more quickly and strongly to (E)-"-caryophylene than the original one (Hiltpold et al, 2010a). As the selection did not impair the infectiousness of the EPNs (Hiltpold et al, 2010b), both populations were tested in the field and were exposed to two maize cultivars either emitting or lacking the ability to emit (E)-"-caryophylene (Hiltpold et al, 2010a;. The application of EPNs significantly reduced the survival of D. v. virgifera irrespective of maize cultivars.…”
Section: Use/selection For a More Competitive Species Or Populationmentioning
confidence: 93%
See 1 more Smart Citation
“…Heterorhabditis bacteriophora Poinar (Rhabditida: Heterorhabditidae), for instance, is highly effective against WCR larvae (Jackson, 1996; Toepfer et al, 2008; Pilz et al, 2009) but is not attracted to EβC (Hiltpold et al, 2010a,c). Selective breeding of H. bacteriophora , however, can increase the attraction of infective juveniles to EβC-emitting maize roots, thereby increasing WCR mortality (Hiltpold et al, 2010a,b). …”
Section: Impact Of Plant Traits On Biological Controlmentioning
confidence: 99%